Defining cutaneous leishmaniasis transmission cycles in colombia through prediction and validation of vectors, reservoirs and parasites involved. (2018)
The Leishmaniases are a group of neglected tropical diseases caused by different species of the protozoan parasite Leishmania, transmitted to its mammalian hosts by the bites of different species of female Phlebotominae sandflies. Many factors have contributed to the disease shifts in its distribution, and changes in its eco epidemiological outcomes have been reported, resulting in the notification of CL outbreaks in new municipalities as well as the incrimination of vectors in unreported regions. The development of new research strategies is vital for establishing the new paradigms of the present transmission cycles, hoping to facilitate the implementation of new mitigation strategies that will reduce parasite transmission. Hereafter the objective of this work is to model and validate the current transmission cycles of cutaneous Leishmaniasis in Colombia defined by the vector and mammal species distribution and interaction in such areas. The work consisted of i) construction of biotic interaction networks and ii)...